PEMBERDAYAAN MAHASISWA ILMU HUKUM MELALUI BIMBINGAN TEKNIS PENYUSUNAN KARYA ILMIAH BERBASIS KECERDASAN BUATAN (AI) - Rosadi, Otong; Afrinal, Afrinal (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study aims to identify the challenges faced by law students in conducting legal research and writing academic papers, as well as to evaluate the effectiveness of artificial intelligence (AI)-based technical guidance in addressing these challenges. The research employs a normative and empirical juridical approach, with data collected through questionnaires distributed to participants of the technical guidance and literature studies. The findings reveal that most students struggle to determine research topics, formulate problems, select relevant theories, and construct logical frameworks. However, after participating in AI-based technical guidance, their understanding and skills in legal academic writing improved significantly. AI, particularly ChatGPT, proved to be an effective tool for accelerating the writing process, formulating legal arguments, and exploring references. Nonetheless, AI usage must be carried out responsibly, considering academic ethics, paraphrasing skills, and a strong grasp of legal research methodology. These findings highlight the need for AI literacy training and the development of academic policies that govern ethical AI usage in higher education institutions.